Communities of Practice: A Strategy for Re-engaging Out-of-School Youth by Nurturing Prospects and Fostering Connections - Diez, Liza; Salvador, Marisol C; Oris, Rowena C.; Malioat, Jocelyn J.; Samson, Jomari; Fabro, Arrianne Michelle F. (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2024)
This research focuses on the potential of the Communities of Practice (CoPs) that might be utilized to bring back the out-of-school youth (OSY) to formal schooling. Even with the attempts to increase enrollment in schools, some of the Filipino youths still have no access to education, and still have difficult life struggles that include loss of jobs and social exclusion. This study discusses the experience and issues with which OSY encounter in CoPs and comprises the valuable prospects for them further. The exploratory research question of the study depicts the experiences of OSY within CoPs in terms of the sense of belonging, social connectedness, and perceived upcoming possibilities. It also narrows down challenges like; they lack financial capital, or have lack of access to services. Subjects of the study were selected within the area of Barangay Nagtenga, Sta. Cruz, Ilocos Sur. Participants and observations were obtained through interviews, and fundamental trends such as isolation, restricted social relationships, and low earnings were identified. From the study, there is a recommended plan on how to bring about the CoPs that focus on the learning from peers, skills enhancement, and community activities for the enhancement of OSY. This research clearly brings out the significance that can be achieved through community-Based strategies in re-engaging and promoting out-of-school youth.